(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study focused on the challenges encountered by unvaccinated employees in Barangay Nagkaisang Nayon, Novaliches, Quezon City. The purpose of this study was to determine the challenges encountered by unvaccinated employees and to assist them through proposed recommendations and solutions to overcome and minimize the problems and challenges that they are facing. Purposive sampling was conducted at Barangay Nagkaisang Nayon in Novaliches, Quezon City. Survey questionnaires were used in the quantitative research design. It was determined that the challenges that unvaccinated employees encounter are their fear of being vaccinated because of the possible side effects that they might experience and their belief that getting the COVID-19 vaccine would cause infertility in female employees. Transportation and discrimination were also some of the challenges that unvaccinated employees faced since they were not allowed to ride public transportation without presenting a vaccination card. In terms of discrimination at their workplace, it is visible that there is unfair treatment between vaccinated and unvaccinated employees and that with the help of proposed recommendations and solutions, the challenges that unvaccinated employees encounter could be minimized. Results showed that the reasons for being unvaccinated were in terms of Fear of Being Vaccinated. Results showed that some unvaccinated respondents are afraid of getting vaccinated because they are worried about the possible side effects. Vaccine Allergy – results showed that the respondents to the study strongly agreed that employees who are allergic to any type of vaccine or injectable medication must first consult with their doctors before getting vaccinated. Pregnancy Issues – most of the respondents believed that getting vaccinated while pregnant would result in infertility. The results showed the challenges encountered by the unvaccinated respondents in terms of transportation. Results showed that the respondents to the study strongly agreed that employees who have not been immunized are not allowed to use public transit. Discrimination – results showed that some of the respondents strongly agreed that several employees said they were limited in their travel around the office, while others were laid off. And, Work Environment – the respondents strongly agreed that there is unfair treatment between vaccinated and unvaccinated employees at their workplace. The proposed solutions for the challenges encountered by the unvaccinated respondents addressed the challenges and encouraged not only the unvaccinated employees but also their coworkers and employers to minimize and avoid possible future challenges. The results of the present study strongly confirm that there are several challenges faced by unvaccinated employees. The researchers advised unvaccinated employees, employers, and their coworkers to strictly follow the COVID-19 rules and regulations to avoid contracting and transmitting the virus. The researchers also recommend that employers educate and inform their employees about the COVID-19 virus and vaccinations. The employees who received discrimination and judgments from their coworkers should be ignored, and the researchers recommend that they focus on improving their performance at work. Unvaccinated employees should always be aware of their surroundings and the people they encounter, and they should always wear a facemask.